Brevibacterium liquefaciens adenylate cyclase and its in vivo stimulation by pyruvate. - Lynch, T J (1975)
Adenylate cyclase of Brevibacterium liquefaciens depends on pyruvate for activity. Growing in a simple medium containing glucose and DL-alanine, the microorganism excreted pyruvate, which reached 20 mM in the medium at stationary phase. Using [3H]adenosine to label the adenosine 5'-triphosphate pool, we showed that pyruvate in the medium stimulated adenylate cyclase of B. liquefaciens in vivo, in a manner similar to the stimulation observed in vitro. Adenylate cyclase in cells harvested at different phases of growth was equally responsive to exogenous pyruvate, indicating that the allosteric site for pyruvate was present in the enzyme throughout the various phases of cell growth. The specific activity of adenylate cyclase was highest in cells harvested at early log phase; thereafter it declined and was substantially lower at stationary phase. Although adenylate cyclase appears to be activated by pyruvate throughout the life span of the cell, the activity appears not to be critical to cell growth, which was comparable whether the medium contained high or low pyruvate.